Apoptotic effects of acacetin in human colon cancer HT-29 and HCT 116 cells - (:unkn) unknown (My University, 2021)
Aim: Acacetin is a natural flavone compound, which is found in several plants as Robinia pseudoacacia and is demonstrated to have anticancerogenic activities in many types of cancer (e.g., human nonsmall cell lung cancer, and prostate). Colorectal carcinoma (CRC) is one of the serious health problems and is a complex disease. We intended to find a more effective new candidate for the treatment of colon cancer, and hence, we designed this study to investigate the effects of acacetin on CRC (HT-29, HCT 116) in vitro. Methods: The study was carried out with the methods that determine for apoptosis (WST-1, Caspase 3/BCA, Annexin V). Results: Acacetin showed antitumor and apoptosis-inducing effects in the CRC cell lines. Conclusions: Acacetin was effective on CRC cell lines, besides no lethal effect on healthy lung cells (MRC-5).
Keywords: apoptosis; caspase; colorectal; Anticancer; flavonoid